(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
This article examines the impact of artificial intelligence (AI) on the postal and parcel industry in the region, analyzes the current challenges in solving the problems of developing new directions in this area, and develops proposals for the future use of artificial intelligence in postal services.